The challenge of Africa’s nitrogen drought: Some indicators from the Malawian experience - Carr, Stephen (International Food Policy Research Institute, 2014)
Years of continuous cultivation with little or no use of external inputs to restore soil nutrients has resulted in a situation in which crop production in a number of African countries is now limited by nutrient deficiencies – nitrogen, in particular, which is crucial to healthy plant growth. This widespread problem has been described as a “nitrogen drought”. Attempts to remedy this situation using only organic inputs have largely failed to keep up with the rate of nutrient loss. This policy note uses Malawi as an example of a country facing these conditions and in which the level of household food production is largely determined by the availability of nitrogen in the soil.